(untitled) (Ha Noi, 2010)
Contents: chapter 1: overview and approach of the Viet Nam country gender assessment; chapter 2: gender, poverty and well being: progress, reversals and barriers; chapter 3: gender and employment: escaping poverty, contributing to growth; chapter 4: gender and political participation; chapter 5: conclusions and recommendations.
Keywords: Gender assessment,Gender assessment